National Health Examination Survey, Cycle II, 1963-1965: Ages 6-11 Years ([Verlag nicht ermittelbar], 1991)
In 1959, the National Health Examination Survey (NHES) began collecting statistics on the medically defined prevalence in the United States population of a variety of specific diseases (using standardized diagnostic criteria) and the distribution of certain physical, physiological, and psychological measurements. The NHES was conducted as a series of survey programs called "cycles." Each cycle was limited to a specific age segment of the population and to certain aspects of the health of that population. The NHES Cycle II contains demographic data on children 6 to 11 years of age, as well as information on children's medical and developmental history, schooling, psychological testing results, physical examinations, hearing, vision, and dental examinations, body measurements, and assessments of skeletal maturation.